AB0348 Transcriptional Activity of Adipose Tissue May BE an Early Marker of Cardiovascular Risk in Rheumatoid Arhtritis. (10th June 2014) - Nadali, M.; Pullerits, R.; Bokarewa, M.; Andersson, K.; Täryö Silfverswärd, S.
Abstract : Background: Rheumatoid arthritis (RA) is an established risk factor for premature development of cardiovascular disease. Adipokines are signal molecules originating from adipose tissue and exhibit strong proinflammatory effects. We have previously shown that resistin utilizes IGF-1R and TLR4 pathway to induce inflammation in RA synovia. Objectives: In the present study we evaluated the role of adipokines and adipokine-related genes on the cardiovascular risk in RA. Methods: Cariovascular risk was estimated in 146 RA patients, all women (median age 57.5 years, range 21-71, median disease duration 8.0 years, range 1-49 years), using the modified Systematic Coronary Risk Evaluation (mSCORE). Serum levels of adipokines and IGF-1 were analyzed by ELISA. mRNA levels of IGF-1R, TLR4, Akt1, STAT3, RETN, and RELA (NF-kB) were analysed in peripheral blood leukocytes and in subcutaneous adipose tissue, using qPCR. The gene expression analysis was performed in the subgroup of younger RA patients (n=54, mean age 46 years, median mSCORE=1). The adipokine levels and gene expression were analyzed in relation to mSCORE. Results: mSCORE was directly related on the age, disease duration, smoking habits and blood fat profile (cholestrol and triglycerides), and not to the DAS28 and BMI of RA patients. mSCORE correlated to the serum levels of leptin, resistin and visfatin. The patients with the increased cardiovascular risk (mSCORE≥1, n=86) had higher levels of adiponectin and visfatin, and low levels of IGF-1 and Akt1 mRNA in the peripheral blood leukocytes compared to the patients where cardiovascular risk was below detection level (mSCORE<1, n=56). In the subgroup of younger patients, serum resistin correlated to mSCORE and to the systemic inflammation but not to DAS28. Additionally, mSCORE showed a strong correlation to the adipocyte expression of resistin-triggering receptors (IGF1-R and TLR4) and to the mediators of their transcriptional signalling Akt, STAT3, and RELA. We observed no correlation between mSCORE and the transcriptional activity of the peripheral blood leukocytes. The correlation of mSCORE and transcriptional activity in adipocytes was not dependent on BMI and was stronger in the normal weight patients. Conclusions: This pilot study shows a correlation between the cardiovascular risk and the transcriptional activity of the subcutaneous adipose tissue in women with RA. The expression of resistin-related genes in adipose tissue in younger women suggests that resistin may be a sufficient force supporting persistent transcriptional activity of adipocytes and driving premature cardiovascular disease in RA patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3893